Ultrahigh-voltage direct-current shielding material and preparation method thereof

The MXene-ionic liquid modified carbon black is used to form a composite conductive agent, which solves the problems of conductive carbon black agglomeration and space charge generation, improves the surface smoothness and conductivity of ultra-high voltage DC cables, and extends the stable running time of the cable.

CN119286120AActive Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411485779.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The shielding material of ultra-high voltage DC cables is prone to agglomeration when using conductive carbon black, affecting the surface finish, and the generation of space charge will lead to cable breakdown, which has failed to effectively solve these problems.

Method used

By introducing MXene-ionic liquid to modify superconducting carbon black, a carbon black-MXene-ionic liquid composite conductive agent is formed, the amount of carbon black is reduced, the uniform dispersion of conductive fillers is achieved, the generation of surface protrusions is reduced, and the ionic liquid and The synergistic conductivity of MXene reduces the PTC effect and the generation of space charge.

Benefits of technology

It improves the surface smoothness of the shielding material, reduces the PTC effect and the generation of space charge, extends the stable running time of the cable, and meets the requirements of ultra-high voltage DC cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098673600000141
    Figure BDA0005098673600000141
  • Figure BDA0005098673600000151
    Figure BDA0005098673600000151
Patent Text Reader

Abstract

The invention discloses an ultrahigh-voltage direct-current shielding material and a preparation method thereof, and the shielding material is prepared from the following raw materials in parts by mass: 65-80 parts, preferably 70-80 parts, of matrix resin; 15 to 25 parts of carbon black-MXene-ionic liquid composite conductive agent, preferably 18 to 23 parts of carbon black-MXene-ionic liquid composite conductive agent; 0.2 to 5 parts of an antioxidant, preferably 0.5 to 2.5 parts of the antioxidant; 1-2 parts, preferably 1-1.5 parts, of a lubricant; 0.5 to 2 parts of cross-linking agent, preferably 0.8 to 1.2 parts of cross-linking agent. By introducing the MXene-ionic liquid modified superconductive carbon black, the conductive effect is improved, the use amount of the carbon black is reduced, and uniform dispersion of the conductive filler is realized, so that the generation of surface bulges is reduced, the surface smoothness of the shielding material is improved, and meanwhile, due to the synergistic conductive effect of the ionic liquid and MXene, the shielding material has good conductivity. The PTC effect of the shielding material is reduced; and the generation of space charges is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable material processing, and in particular to an ultra-high voltage direct current shielding material and a preparation method thereof. Background Art

[0002] Ultra-high voltage direct current transmission has the characteristics of long distance, large capacity and low cost, and is widely used in the field of submarine cables. As an indispensable and important component of ultra-high voltage cable materials, the stability and economy of shielding materials are particularly important. Ultra-high voltage direct current shielding materials require shielding materials to have the characteristics of ultra-smoothness, low PTC effect and reduced space charge generation, so as to ensure that the DC cable can operate stably for a long time.

[0003] Conductive carbon black has large surface energy and specific surface area, and is prone to agglomeration. Carbon black agglomeration is one of the important reasons that affect the surface finish of ultra-high voltage shielding materials. In CN116120655A, ionic liquids are used to modify conductive carbon black, which solves the bulge problem caused by carbon black agglomeration and improves the surface finish, but does not involve the impact on the generation of space charge. Space charge refers to the charge accumulated inside or on the interface of a dielectric, which will cause disturbances in the electric field distribution and may cause cable breakdown. In dielectrics, the generation of space charge may be due to the uneven distribution of charge carriers, such as the capture and release of electrons, holes or ions. Therefore, it is also particularly important to reduce the generation of space charge. Summary of the invention

[0004] The main purpose of the present invention is to provide an ultra-high voltage direct current shielding material and a preparation method thereof, which improves the conductive effect, reduces the amount of carbon black, and realizes the uniform dispersion of the conductive filler by introducing MXene-ionic liquid to modify superconducting carbon black, thereby reducing the generation of surface protrusions and improving the surface smoothness of the shielding material. At the same time, due to the synergistic conductive effect of ionic liquid and MXene, the PTC effect of the shielding material is reduced and the generation of space charge is reduced.

[0005] In order to achieve one aspect of the above purpose, the present invention adopts the following technical solution: an ultra-high voltage DC shielding material, calculated by mass, comprises the following raw materials:

[0006] 65-80 parts of base resin, preferably 70-80 parts;

[0007] 15 to 25 parts of carbon black-MXene-ionic liquid composite conductive agent, preferably 18 to 23 parts;

[0008] 0.2 to 5 parts of antioxidant, preferably 0.5 to 2.5 parts;

[0009] 1 to 2 parts of lubricant, preferably 1 to 1.5 parts;

[0010] 0.5 to 2 parts of cross-linking agent, preferably 0.8 to 1.2 parts;

[0011] The carbon black-MXene-ionic liquid composite conductive agent is carbon black modified with MXene and imidazole conductive ionic liquid.

[0012] In some specific embodiments, the base resin comprises one or more of ethylene-vinyl acetate copolymer EVA, ethylene-butyl acrylate copolymer EBA, ethylene-methyl acrylate copolymer EMA, and ethylene-ethyl acrylate copolymer EEA, preferably EBA resin or EMA resin, and more preferably EBA resin.

[0013] In some specific embodiments, the mass fraction of the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer is 15-30%, preferably 16-20%, and more preferably 16-19%; the mass fraction of the butyl acrylate monomer unit in the ethylene-butyl acrylate copolymer is 15-25%, preferably 16-20%, and more preferably 16-19%; the mass fraction of the methyl acrylate monomer unit in the ethylene-methyl acrylate copolymer is 15-25%, preferably 16-20%, and more preferably 16-19%.

[0014] In some specific embodiments, the imidazole conductive ionic liquid is 1-vinyl-3-butylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium tetrafluoroborate.

[0015] In some specific embodiments, the method for preparing the carbon black-MXene-ionic liquid composite conductive agent comprises the following steps:

[0016] 1) heating the MXene and the ionic liquid under stirring to react, crushing and separating the reactants to obtain a solid and drying it to obtain the MXene modified with the ionic liquid;

[0017] 2) The ionic liquid modified MXene obtained in step 1) is mixed with carbon black to obtain a dispersion, and the dispersion is ground to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0018] In some specific embodiments, in the step 1), the mass ratio of MXene to ionic liquid is 5-6:1-1.5, exemplarily 5:1, 5.5:1, 6:1, 5:1.5, 5.5:1.5, 6:1.5, etc.

[0019] In some specific embodiments, in step 1), the stirring conditions include: stirring time of 40-60 min, stirring speed of 400-600 r / min, exemplarily 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, etc.

[0020] In some specific embodiments, in step 1), the heating temperature is 120-170°C, exemplarily 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, etc.

[0021] In some specific embodiments, in the step 1), the reaction is carried out in a microwave reactor, and the pulverization treatment is carried out in a cell pulverizer, preferably the pulverization treatment time is 30-50 min, and the preferred vibration frequency is 50-80 kHz.

[0022] In some specific embodiments, in step 1), the centrifugation is performed in a centrifuge, and the centrifugation conditions include: a centrifugal speed of 8000-10000 r / min, and a centrifugal time of 5-10 min.

[0023] In some specific embodiments, in step 1), the drying conditions include: a drying temperature of 80-90° C. and a drying time of 8-10 h.

[0024] In some specific embodiments, in step 2), the ionic liquid-modified MXene and carbon black are dispersed in an organic solvent, and a dispersant is added to obtain a dispersed solution.

[0025] Preferably, the solvent is one or more of ethylene glycol monobutyl ether and diethylene glycol monobutyl ether, and the dispersant is one or more of polyvinyl pyrrolidone and polyvinyl alcohol.

[0026] Preferably, the mass ratio of carbon black: ionic liquid modified MXene: solvent: dispersant is 1:3-8:90-95:1-3.

[0027] In some specific embodiments, in the step 2), the ionic liquid-modified MXene and carbon black are ultrasonically dispersed in an organic solvent. Preferably, the ultrasonic time is 1 to 3 hours, the ultrasonic temperature is 25 to 40° C., and the ultrasonic frequency is 40,000-60,000 Hz.

[0028] In some specific embodiments, in step 2), the grinding method is selected from ball milling, vibration milling, air flow milling, stirring milling, planetary ball milling, and high pressure roller milling, preferably ball milling.

[0029] In some specific embodiments, the ball milling conditions include: a ball milling speed of 200-300 r / min, and a ball milling time of 1-2 h.

[0030] In a preferred embodiment, the method for preparing the carbon black-MXene-ionic liquid composite conductive agent comprises the following steps:

[0031] S1: Take 5-6 parts of MXene and 1-1.5 parts of ionic liquid and place them in a microwave reactor, heat to 120-170°C, preferably stir for 40-60 min, preferably stir at a speed of 400-600 r / min, then treat with a cell crusher for 30-50 min, preferably vibrate at a frequency of 50-80 kHz, centrifuge at 8000-10000 r / min for 5-10 min, take the supernatant and add dichloromethane and ethanol respectively, centrifuge for 15-20 min, retain the solid, repeat 2-3 times, place the obtained black solid in a vacuum drying oven and dry at 80-90°C for 8-10 h to obtain MXene modified with ionic liquid;

[0032] S2: Ultrasonic dispersion of the ionic liquid modified MXene and carbon black prepared in S1 in an organic solvent, adding a dispersant, preferably the solvent is one of ethylene glycol monobutyl ether and diethylene glycol monobutyl ether, and the dispersant is one of polyvinyl pyrrolidone and polyvinyl alcohol; the preferred mass ratio of carbon black: ionic liquid modified MXene: solvent: dispersant is 1:3-8:90-95:1-3; the treated dispersion is ball milled in a ball mill at 200-300r / min for 1-2h to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0033] In some specific embodiments, the antioxidant is one or more of antioxidant 300, antioxidant 1010, and antioxidant 1076, preferably antioxidant 300; the lubricant is one or more of polyethylene wax, zinc stearate, and stearamide, preferably polyethylene wax; the cross-linking agent is one or more of diisopropylbenzene peroxide and di-tert-butyl diisopropylbenzene peroxide.

[0034] Another aspect of the present invention also provides a method for preparing an ultra-high voltage direct current shielding material, comprising the following steps:

[0035] The base resin, carbon black-MXene-ionic liquid composite conductive agent, antioxidant and lubricant are mixed, filtered, extruded, granulated and dried, and a cross-linking agent is added for post-absorption to obtain a shielding material.

[0036] In some specific embodiments, the mixing is performed in a reciprocating mixer, the mixing part of the reciprocating mixer is a reciprocating single-screw extruder, and the molten material processed in the reciprocating mixer is filtered through a filtering system.

[0037] In some specific embodiments, the cross-linking agent is atomized and added for post-absorption. Preferably, the temperature of the post-absorption process is 60-80°C, exemplarily 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the time of the post-absorption process is 1-3h.

[0038] Compared with the prior art, the present invention has the following advantages: the ultra-high voltage DC shielding material provided by the present invention is made of the following raw materials by mass: 65-80 parts of matrix resin; 15-25 parts of carbon black-MXene-ionic liquid composite conductive agent; 0.2-5 parts of antioxidant; 1-2 parts of lubricant; 0.5-2 parts of cross-linking agent. Among them, carbon black is spherical and is easy to form grape-like enriched bodies after processing; MXene is a two-dimensional layered conductive material with a layered crystal structure. The conductivity of MXene comes from the metal layers in its layered structure. These metal layers provide free electrons, making the material have metal-like conductivity. In addition, the interlayer distance of MXene is large, which facilitates the insertion and deintercalation of ions and molecules, thereby affecting its conductive properties; ionic liquids can generate current through the migration of anions and cations and conduct electricity.

[0039] The present invention reduces the amount of traditional carbon black by introducing MXene-ionic liquid modified carbon black material, improves the processing performance of the material, and realizes the uniform dispersion of conductive fillers, thereby reducing the generation of surface protrusions, thereby avoiding the electric field concentration and breakdown caused by impurities and air gaps, and improving the surface smoothness of the shielding material. At the same time, on the one hand, the layered structure of MXene and the grape-shaped structure of carbon black are in contact with each other, which can form a double-penetration conductive network, and then form a complete electronic conductive network structure. On the other hand, due to the intervention of ionic liquid, through ion migration between MXene layers, electrons and ions conduct electricity synergistically, which can improve the conductivity of the overall conductive agent and reduce the PTC effect of the shielding material. The generation of space charge is also reduced by the introduction of diversified conductors (carbon black-MXene-ionic liquid composite).

[0040] Specifically, the mechanism of MXene grafted ionic liquids suppressing space charge may involve the following aspects:

[0041] 1. Electronic conductivity: The high electronic conductivity of the MXene layer can provide a fast electron migration path, help balance the charge distribution inside the material, and reduce the space charge effect caused by the accumulation of electrons or holes.

[0042] 2. Ionic conductivity: The ionic conductivity of ionic liquids ensures that ions can migrate quickly under the action of an electric field, avoiding the formation of localized charge accumulation inside the dielectric. The rapid response of ions helps maintain charge balance, thereby inhibiting the formation of space charge.

[0043] 3. Reduction of interfacial polarization: The interfacial effect between MXene and ionic liquid can reduce interfacial polarization, because ionic liquid can wet the MXene surface, reduce charge traps at the interface, and thus reduce the formation of space charge.

[0044] 4. Chemical stability: The chemical stability of ionic liquids can prevent MXene from degrading in harsh environments, maintain its good conductive properties, and thus continuously suppress the generation of space charge.

[0045] 5. Enhanced dielectric properties: MXene-grafted ionic liquid composites may exhibit enhanced dielectric properties, which helps to better manage the distribution of charge carriers and reduce the accumulation of space charges.

[0046] 6. Capture and release of charge carriers: The layered structure of MXene and the ions in the ionic liquid can work synergistically to reduce the capture and release time of charge carriers in the material and avoid the formation of persistent space charge.

[0047] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION

[0048] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are shown in the examples, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0049] The raw materials, instruments and testing methods used in the embodiments of the present invention are described below. For those not described in detail, reference is made to the prior art.

[0050] Reciprocating mixer: BUSS AG, Switzerland, model: MX-30.

[0051] EBA: Dow Chemical Company of the United States, the mass fraction of butyl acrylate monomer unit is 17%.

[0052] Carbon black: DENKA, acetylene black.

[0053] MXene: Beike New Materials Company, Ti3C2T x .

[0054] Ionic liquids: Qiyue Biotechnology, 1-vinyl-3-butyl imidazole tetrafluoroborate; Shandong Deke Biotechnology Co., Ltd., 1-butyl-3-methyl imidazole tetrafluoroborate;

[0055] Polyethylene wax: Honeywell, AC-617A.

[0056] Antioxidant: Ciba Specialty Chemicals, Switzerland, Antioxidant 300.

[0057] BIPB: Arkema.

[0058] Mechanical properties test: The test method is in accordance with ISO 527, ISO 178 and ISO 180, using Instron tensile tester INSTRON 5966.

[0059] Density test: The test method is carried out in accordance with GB / T 1033.1. A square test piece is used with a thickness of 2.0±0.1mm and a side length of 20-25mm.

[0060] Hot stretching: It should be carried out in accordance with GB / T 2951.5. Sample preparation should be carried out in accordance with GB / T 1040.2.

[0061] Volume resistivity: The volume resistivity at 23°C shall be measured in accordance with GB / T 3048.3, and the sample shall be conditioned for no less than 24 hours in an environment with a temperature of 23±3°C and a relative humidity of 50±5%. The volume resistivity at 90°C shall be measured in accordance with Appendix A of GB / T 3048.3. The volume resistivity at 90°C after heat aging at 135°C for 7 days shall be measured in accordance with Appendix A of GB / T 3048.3, and heat aging shall be carried out in accordance with GB / T 2951.12.

[0062] Surface protrusions: in accordance with the provisions of Appendix A of Q / GDW 11883.2-2018 standard, the detector is the SSA detection equipment of OCS company, and the resolution of the protrusion height should be better than 25μm. Sampling and testing standards: Class 100 clean room.

[0063] Space charge: The test was conducted using the electroacoustic pulse method (PEA), and the test equipment was the solid medium space charge test system built by Shanghai Jiao Tong University. The semi-conductive electrode used the shielding materials of the embodiment and the comparative example, and the insulating layer used LE0550DC from Borealis. The FEF parameter was introduced to characterize the space charge. where v peak is the peak height (mV) of the ground electrode signal voltage when high voltage U=40kv is applied; v peak,cal It is a low voltage U in the absence of space charge. cal The peak height of the signal voltage (mV) at the ground electrode when the calibration measurement is performed at (kV). In the case of heterogeneous charges close to the ground electrode, the electric field will be higher than the calculated field assuming no space charge, i.e. FEF>1. Conversely, when homogeneous charges are present, the field is lower, i.e. FEF<1. The optimal value is FEF=1, indicating that space charge has no effect on the ground electrode electric field. The closer the FEF value is to 1, the less space charge is generated.

[0064] Preparation Example 1

[0065] Take 5 parts by mass of MXene and 1 part by mass of 1-vinyl-3-butyl imidazole tetrafluoroborate ionic liquid and place them in a microwave reactor, heat to 150°C, set the stirring speed to 500rpm and stir for 60min. Then treat with a cell crusher for 30min with a vibration frequency of 80kHz. Centrifuge at 10000r / min for 10min, take the supernatant and add dichloromethane and ethanol in batches, centrifuge for 20min each, retain the solid, and repeat 3 times. Place the obtained black solid in a vacuum drying oven and dry it at 90°C for 8h to obtain MXene modified with ionic liquid.

[0066] The prepared ionic liquid modified MXene and acetylene carbon black were ultrasonically dispersed in ethylene glycol monobutyl ether solvent at a temperature of 35°C, an ultrasonic frequency of 50,000 Hz, and an ultrasonic time of 2 hours. Polyvinyl pyrrolidone was then added, wherein the mass fraction ratio of superconducting carbon black: ionic liquid modified MXene: ethylene glycol monobutyl ether solvent: polyvinyl pyrrolidone was 1:5:92:2. The treated dispersion was ball milled in a ball mill at a speed of 300 r / min for 2 hours to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0067] Preparation Example 2

[0068] Take 6 parts by mass of MXene and 1.5 parts by mass of 1-vinyl-3-butyl imidazole tetrafluoroborate ionic liquid and place them in a microwave reactor, heat to 170°C, set the stirring speed to 500rpm and stir for 60min. Then treat with a cell crusher for 30min with a vibration frequency of 80kHz. Centrifuge for 10min at 10000r / min, take the supernatant and add dichloromethane and ethanol in batches, centrifuge for 20min each, retain the solid, and repeat 3 times. Place the obtained black solid in a vacuum drying oven and dry it at 90°C for 8h to obtain MXene modified with ionic liquid.

[0069] The prepared ionic liquid modified MXene and acetylene carbon black were ultrasonically dispersed in ethylene glycol monobutyl ether solvent at a temperature of 35°C, an ultrasonic frequency of 50,000 Hz, and an ultrasonic time of 2 hours. Polyvinyl pyrrolidone was then added, wherein the mass fraction ratio of superconducting carbon black: ionic liquid modified MXene: ethylene glycol monobutyl ether solvent: polyvinyl pyrrolidone was 1:5:92:2. The treated dispersion was ball milled in a ball mill at a speed of 300 r / min for 2 hours to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0070] Preparation Example 3

[0071] Take 5 parts by mass of MXene and 1 part by mass of 1-vinyl-3-butyl imidazole tetrafluoroborate ionic liquid and place them in a microwave reactor, heat to 150°C, set the stirring speed to 500rpm and stir for 60min. Then treat with a cell crusher for 30min with a vibration frequency of 80kHz. Centrifuge at 10000r / min for 10min, take the supernatant and add dichloromethane and ethanol in batches, centrifuge for 20min each, retain the solid, and repeat 3 times. Place the obtained black solid in a vacuum drying oven and dry it at 90°C for 8h to obtain MXene modified with ionic liquid.

[0072] The prepared ionic liquid modified MXene and acetylene carbon black were ultrasonically dispersed in ethylene glycol monobutyl ether solvent at a temperature of 35°C, an ultrasonic frequency of 50,000 Hz, and an ultrasonic time of 2 hours. Polyvinyl pyrrolidone was then added, wherein the mass fraction ratio of superconducting carbon black: ionic liquid modified MXene: ethylene glycol monobutyl ether solvent: polyvinyl pyrrolidone was 1:5:93:1. The treated dispersion was ball milled in a ball mill at a speed of 300 r / min for 2 hours to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0073] Preparation Example 4

[0074] Take 5 parts by mass of MXene and 1 part by mass of 1-vinyl-3-butyl imidazole tetrafluoroborate ionic liquid and place them in a microwave reactor, heat to 150°C, set the stirring speed to 600rpm and stir for 60min. Then treat with a cell crusher for 50min with a vibration frequency of 80kHz. Centrifuge for 10min at 10000r / min, take the supernatant and add dichloromethane and ethanol in batches, centrifuge for 20min each, retain the solid, and repeat 3 times. Place the obtained black solid in a vacuum drying oven and dry it at 90°C for 8h to obtain MXene modified with ionic liquid.

[0075] The prepared ionic liquid modified MXene and acetylene carbon black were ultrasonically dispersed in ethylene glycol monobutyl ether solvent at a temperature of 35°C, an ultrasonic frequency of 50,000 Hz, and an ultrasonic time of 2 hours. Polyvinyl pyrrolidone was then added, wherein the mass fraction ratio of superconducting carbon black: ionic liquid modified MXene: ethylene glycol monobutyl ether solvent: polyvinyl pyrrolidone was 1:5:92:2. The treated dispersion was ball milled in a ball mill at a speed of 300 r / min for 2 hours to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0076] Preparation Example 5

[0077] Take 5 parts by mass of MXene and 1 part by mass of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and place them in a microwave reactor, heat to 150°C, set the stirring speed to 500rpm and stir for 60min. Then treat with a cell crusher for 30min with a vibration frequency of 80kHz. Centrifuge at 10000r / min for 10min, take the supernatant and add dichloromethane and ethanol in batches, centrifuge for 20min each, retain the solid, and repeat 3 times. Place the obtained black solid in a vacuum drying oven and dry it at 90°C for 8h to obtain MXene modified with ionic liquid.

[0078] The prepared ionic liquid modified MXene and acetylene carbon black were ultrasonically dispersed in ethylene glycol monobutyl ether solvent at a temperature of 35°C, an ultrasonic frequency of 50,000 Hz, and an ultrasonic time of 2 hours. Polyvinyl pyrrolidone was then added, wherein the mass fraction ratio of superconducting carbon black: ionic liquid modified MXene: ethylene glycol monobutyl ether solvent: polyvinyl pyrrolidone was 1:5:92:2. The treated dispersion was ball milled in a ball mill at a speed of 300 r / min for 2 hours to obtain a carbon black-MXene-ionic liquid composite conductive agent.

[0079] Example 1

[0080] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 76 parts of EBA resin, 22 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0081] This embodiment provides a method for preparing a cable shielding material, comprising the following steps:

[0082] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 180°C, the plasticizing section temperature is 190°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; during extrusion granulation, the die temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0083] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0084] Example 2

[0085] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 76 parts of EBA resin, 22 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 2), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0086] This embodiment provides a method for preparing a cable shielding material, comprising the following steps:

[0087] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 2), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 180°C, the plasticizing section temperature is 190°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; during extrusion granulation, the die temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0088] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0089] Example 3

[0090] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 76 parts of EBA resin, 22 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 3), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0091] This embodiment provides a method for preparing a cable shielding material, comprising the following steps:

[0092] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 3), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 180°C, the plasticizing section temperature is 190°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; during extrusion granulation, the die temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0093] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0094] Example 4

[0095] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 76 parts of EBA resin, 22 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 4), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0096] This embodiment provides a method for preparing a cable shielding material, comprising the following steps:

[0097] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 4), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 180°C, the plasticizing section temperature is 190°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; during extrusion granulation, the die temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0098] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0099] Example 5

[0100] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 80 parts of EBA resin, 18 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0101] This embodiment provides a method for preparing an ultra-high voltage cable shielding material, comprising the following steps:

[0102] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing temperature is 75°C in the feeding section, 180°C in the melting section, 190°C in the plasticizing section, 200°C in the extrusion section, and the screw speed is 320 rpm / min; during extrusion granulation, the head temperature is 200°C, the melt pressure is 7-7.5 MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0103] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0104] Example 6

[0105] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 73 parts of EBA resin, 25 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0106] This embodiment provides a method for preparing an ultra-high voltage cable shielding material, comprising the following steps:

[0107] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing temperature is 75°C in the feeding section, 180°C in the melting section, 190°C in the plasticizing section, 200°C in the extrusion section, and the screw speed is 320 rpm / min; during extrusion granulation, the head temperature is 200°C, the melt pressure is 7-7.5 MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0108] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0109] Example 7

[0110] The present embodiment provides an ultra-high voltage cable shielding material, which includes, by weight, 76 parts of EBA resin, 22 parts of carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 5), 0.5 parts of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB.

[0111] This embodiment provides a method for preparing a cable shielding material, comprising the following steps:

[0112] (1) EBA resin, carbon black-MXene-ionic liquid composite conductive agent (Preparation Example 1), antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, and extruded under pressure by a melt pump. The melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 180°C, the plasticizing section temperature is 190°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; during extrusion granulation, the die temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 60°C.

[0113] (2) The BIPB cross-linking agent is atomized and passed into a shaking tank to perform a post-absorption process with the pellets obtained in step (1), and the mixture is kept at 70° C. for 24 hours to ensure that the cross-linking agent is completely absorbed. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0114] Comparative Example

[0115] This comparative example provides an ultra-high voltage cable shielding material, which includes 62.5 parts of EBA resin, 35 parts of conductive carbon black, 1 part of antioxidant 300, 1.5 parts of polyethylene wax and 1 part of BIPB by weight. The conductive carbon black is commercially available Cabot carbon black VXC500. This comparative example provides a method for preparing a cable shielding material, comprising the following steps:

[0116] EBA resin, conductive carbon black, antioxidant 300 and polyethylene wax are added to a reciprocating mixer for mixing, filtered in a screen changer, extruded under pressure by a melt pump, and the melt is granulated by an underwater granulation system and air-dried to obtain a resin composite material; the mixing and feeding section temperature is 80°C, the melting section temperature is 160°C, the plasticizing section temperature is 180°C, the extrusion section temperature is 190°C, and the screw speed is 300rpm; in extrusion granulation, the head temperature is 200°C, the melt pressure is 7-7.5MPa, the underwater pelletizing temperature is 40°C, and the air-drying temperature is 70°C. The material is continuously sampled for impurity detection, and finally the finished product is packaged to obtain the cable shielding material.

[0117] The sample preparation method adopts the particle molding method, which is carried out according to the provisions of 6.2.1 in JB / T 10738-2007. The test piece should be flat, smooth, uniform in thickness, and free of bubbles. The thickness of the test piece should comply with the provisions of each test item. The test standard is carried out in accordance with Q / GDW11883.2-2018, and the standard values ​​are shown in the table. According to the standard requirements, the embodiments and comparative examples were tested, and the results are shown in Table 1.

[0118] Table 1 Main physical properties of each embodiment and comparative example

[0119]

[0120]

[0121] It can be seen from the data in Table 1 that the basic properties of the cable shielding materials prepared by the compositions in Examples 1-7 have reached the indicators specified in Q / GDW 11883.2-2018. Compared with the examples, the mechanical properties of the comparative example deteriorate, and the surface protrusions seriously fail to meet the standards. The reason is that the conductive carbon black cannot be evenly dispersed, resulting in the deterioration of various properties. Compared with Example 1, the amount of ionic liquid used in Example 2 is relatively increased, and the resistance is slightly increased. The reason is that the reduction of the MXene layered structure leads to imperfect formation of the conductive network. The dispersant used in Example 3 is reduced, the mechanical properties of the material deteriorate, and a small part of the protrusions appear. The reason is that the conductive agent is not completely dispersed and agglomerated. In Example 4, the speed of Preparation Example 4 is increased, the cell crusher crushing time is increased, the resistance becomes larger, and the FEF parameter increases. The reason is that the preparation conditions are severe and the structure of the composite conductive agent begins to be destroyed. Example 5 reduces the number of composite conductive agents, and Example 6 increases the number of composite conductive agents used, and its performance is within the standard range. Preparation Example 5 used in Example 7 uses 1-butyl-3-methylimidazolium tetrafluoroborate imidazole ionic liquid, and all effects are within the standard range.

[0122] From the above comparison, it can be seen that the ultra-high voltage cable shielding material prepared by the present invention meets the ultra-high voltage requirements, and greatly reduces the number of surface protrusions of the shielding material, greatly improves the smoothness of the material, and improves the conductivity of the material, reducing the PTC effect. At the same time, the use of the composite conductive agent reduces the generation of space charge.

[0123] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. An ultra-high voltage direct current shielding material, characterized in that: The composition comprises the following raw materials by weight: 65-80 parts of base resin, preferably 70-80 parts; 15 to 25 parts of carbon black-MXene-ionic liquid composite conductive agent, preferably 18 to 23 parts; 0.2 to 5 parts of antioxidant, preferably 0.5 to 2.5 parts; 1 to 2 parts of lubricant, preferably 1 to 1.5 parts; 0.5 to 2 parts of cross-linking agent, preferably 0.8 to 1.2 parts; The carbon black-MXene-ionic liquid composite conductive agent is carbon black modified with MXene and imidazole conductive ionic liquid.

2. The ultra-high voltage direct current shielding material according to claim 1, characterized in that: The matrix resin comprises one or more of ethylene-vinyl acetate copolymer EVA, ethylene-butyl acrylate copolymer EBA, ethylene-methyl acrylate copolymer EMA, and ethylene-ethyl acrylate copolymer EEA, preferably EBA resin or EMA resin, more preferably EBA resin; Preferably, the mass fraction of the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer is 15-30%, further preferably 16-20%, and more preferably 16-19%; the mass fraction of the butyl acrylate monomer unit in the ethylene-butyl acrylate copolymer is 15-25%, further preferably 16-20%, and more preferably 16-19%; the mass fraction of the methyl acrylate monomer unit in the ethylene-methyl acrylate copolymer is 15-25%, further preferably 16-20%, and more preferably 16-19%.

3. The ultra-high voltage direct current shielding material according to claim 1, characterized in that: The preparation method of the carbon black-MXene-ionic liquid composite conductive agent comprises the following steps: 1) heating MXene and ionic liquid to react under stirring, crushing and separating the reactants to obtain a solid and drying it to obtain MXene modified with ionic liquid; 2) The ionic liquid modified MXene obtained in step 1) is mixed with carbon black in a solution to obtain a dispersion, and the dispersion is ground to obtain a carbon black-MXene-ionic liquid composite conductive agent.

4. The ultra-high voltage direct current shielding material according to claim 3, characterized in that: In the step 1), the mass ratio of MXene to ionic liquid is 5-6:1-1.

5.

5. The ultra-high voltage direct current shielding material according to claim 3 or 4, characterized in that: In the step 1), the stirring conditions include: stirring time of 40-60 min, stirring speed of 400-600 r / min, and heating temperature of 120-170° C.; In the step 1), the reaction is carried out in a microwave reactor, and the crushing treatment is carried out in a cell crusher, preferably the crushing treatment time is 30-50 minutes, and the preferred vibration frequency is 50-80kHz; In the step 1), the centrifugation is performed in a centrifuge, and the centrifugation conditions include: a centrifugal speed of 8000-10000 r / min, and a centrifugal time of 5-10 min; In the step 1), the drying conditions include: drying temperature of 80-90° C., and drying time of 8-10 h.

6. The ultra-high voltage direct current shielding material according to any one of claims 3 to 5, characterized in that: In the step 2), the ionic liquid-modified MXene and carbon black are dispersed in an organic solvent, and a dispersant is added to obtain a dispersed solution; Preferably, the solvent is one or more of ethylene glycol monobutyl ether and diethylene glycol monobutyl ether, and the dispersant is one or more of polyvinyl pyrrolidone and polyvinyl alcohol; Preferably, the mass ratio of carbon black: ionic liquid modified MXene: solvent: dispersant is 1:3-8:90-95:1-3; In the step 2), the ionic liquid modified MXene and carbon black are ultrasonically dispersed in an organic solvent. Preferably, the ultrasonic time is 1 to 3 hours, the ultrasonic temperature is 25 to 40° C., and the ultrasonic frequency is 40000-60000 Hz; In the step 2), the grinding method is selected from one of ball milling, vibration milling, air flow milling, stirring milling, planetary ball milling, and high pressure roller milling, preferably ball milling. The conditions for ball milling include: ball milling speed of 200-300r / min, and ball milling time of 1-2h.

7. The ultra-high voltage direct current shielding material according to any one of claims 3 to 6, characterized in that: The preparation method of the carbon black-MXene-ionic liquid composite conductive agent comprises the following steps: S1: Take 5-6 parts of MXene and 1-1.5 parts of ionic liquid and place them in a microwave reactor, heat to 120-170°C, preferably stir for 40-60 min, preferably stir at a speed of 400-600 r / min, then treat with a cell crusher for 30-50 min, preferably vibrate at a frequency of 50-80 kHz, centrifuge at 8000-10000 r / min for 5-10 min, take the supernatant and add dichloromethane and ethanol respectively, centrifuge for 15-20 min, retain the solid, repeat 2-3 times, place the obtained black solid in a vacuum drying oven and dry at 80-90°C for 8-10 h to obtain MXene modified with ionic liquid; S2: Ultrasonic dispersion of the ionic liquid modified MXene and carbon black prepared in S1 in an organic solvent, adding a dispersant, preferably the solvent is one of ethylene glycol monobutyl ether and diethylene glycol monobutyl ether, and the dispersant is one of polyvinyl pyrrolidone and polyvinyl alcohol; the preferred mass ratio of carbon black: ionic liquid modified MXene: solvent: dispersant is 1:3-8:90-95:1-3; the treated dispersion is ball milled in a ball mill at 200-300r / min for 1-2h to obtain a carbon black-MXene-ionic liquid composite conductive agent.

8. The ultra-high voltage direct current shielding material according to any one of claims 1 to 7, characterized in that: The antioxidant is one or more of antioxidant 300, antioxidant 1010, and antioxidant 1076, preferably antioxidant 300; the lubricant is one or more of polyethylene wax, zinc stearate, and stearamide, preferably polyethylene wax; the cross-linking agent is one or more of diisopropylbenzene peroxide and di-tert-butyl diisopropylbenzene peroxide.

9. The method for preparing the ultra-high voltage direct current shielding material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The base resin, carbon black-MXene-ionic liquid composite conductive agent, antioxidant and lubricant are mixed, filtered, extruded, granulated and dried, and a cross-linking agent is added for post-absorption to obtain a shielding material.

10. The method for preparing the ultra-high voltage direct current shielding material according to claim 9, characterized in that: The mixing is carried out in a reciprocating mixer, the mixing part of the reciprocating mixer is a reciprocating single-screw extruder, and the molten material processed in the reciprocating mixer is filtered through a filtering system; Preferably, the crosslinking agent is atomized and then added for post-absorption, the temperature of the post-absorption process is 60 to 80° C., and the time of the post-absorption process is 1 to 3 hours. 。

Citation Information

Patent Citations

  • Shielding material with improved surface smoothness, preparation method and semi-conductive shielding product

    CN115093639A

  • Preparation method of thermoplastic cable shielding material

    CN115466454A

  • Ionic liquid modified conductive carbon black cable semi-conductive shielding material and preparation method thereof

    CN116120655A

  • Preparation method and application of MXene / ionic liquid composite aerogel

    CN118267940A

  • Conductive material, conductive film, electrochemical capacitor, conductive material production method, and conductive film production method

    US20220157534A1

Cited By

  • Environment-friendly wear-resistant long-acting antistatic PVC aggregate and preparation method thereof

    CN120842754A

  • Environment-friendly long-wearing antistatic PVC granules and preparation method thereof

    CN120842754B